Producers, Distributors, Users and Quality of Services in Education - Želvys, Rimantas (Acta Paedagogica Vilnensia, 2002)
The new project of the Education Act of the Republic of Lithuania introduces a number of new concepts, namely, the concepts of providers and users of educational services. The understanding of educational organizations as service organizations enable us to deal with the problem of quality in education from a new theoretical standpoint. According to McGinn and Welsh (1999), the system of market in education consists of producers, distributors and users. Improving the effectiveness of each segment improves the overall quality of education. The article analyses the role of providers, distributors and users in ensuring the quality of services in education, describes the arising problems in relation to quality assurance and suggests possible solutions. The quality of educational production may be improved by mobilizing additional resources, demonopolization and decentralization of the provision system, as well as changing of psychological attitude towards educational provision. The quality of distribution is mainly determined by the concept of customers. If state is considered to be the main customer, the quality of distribution is defined by standards of education. If students and parents are the main customers, the quality is defined as meeting the needs of individual customers. Finally, the users can also play an important role in improving the quality of education. Users will have more influence on the quality of education if the system will be partially decentralized and privatized, the school community will get more power, the social and teaching functions of educational institutions will be clearly separated and the concept of service university will gain popularity in the sector of higher education.